Geographically Weighted Regression Model of Stunting Determinants in Indonesia - Kurniawati, Dini; Hastono, Sutanto Priyo; Safika, Iko; Wahyuningsih, Wiji (Journal of Maternal and Child Health, 2025)
Background: Stunting is a chronic condition resulting from malnutrition during early growth, potentially affecting physical and cognitive development in children into adults. According to the 2023 Indonesian Health Survey (SKI), stunting in Indonesia remains at 21.5%. This figure is still far from the government's target for 2024, which was below 14%. This study aims to identify the determinants of stunting caused by spatial conditions in Indonesia in 2024. Subjects and Method: This study employed an ecological design with a spatial approach, utilizing aggregate data from the 2023 SKI and 2024 Central Bureau of Statistics (BPS) across 38 provinces in Indonesia. The dependent variable was stunting prevalence, and the analysis included eight independent variables using descriptive statistics, spatial analysis (Moran’s I and Local Moran’s I), multiple linear regression (OLS), and Geographically Weighted Regression (GWR). Data was processed between November 2024 and January 2025 using SPSS, Geoda, and R Studio. Results: Results show that the average stunting prevalence in Indonesia in 2024 was 23.56% (Standard Deviation: 6.80), which unmet the government’s target in the same year. The provinces with the lowest and highest stunting prevalence were Bali (7.2%) and Central Papua (39.3%). Meanwhile, Papua, West Papua, South Papua, Central Papua, and Highlands Papua were provinces with high stunting prevalence and surrounded by similarly high prevalence (high-high) provinces. In contrast, Banten and West Sumatra had high stunting prevalence but were surrounded by provinces with low prevalence (High-Low). Finally, factors influencing stunting across geographical areas included stunting knowledge, completion of immunization coverage, and poverty rates. Conclusion: Efforts to reduce stunting in Indonesia should focus on improving communication, information, and education, particularly in provinces with high prevalence. In addition, increasing coverage and access to complete basic immunization and enhanced family welfare should also be highlighted.